Jobs! Electricity Shortages and Unemployment in Africa - Mensah, Justice Tei (World Bank, Washington, DC, 2018)
This paper presents evidence on how the provision of unreliable electricity constrains expansion in the productive sectors of the economy, consequently leading to a reduction in the number of employment opportunities in Africa. Using geodata on electricity transmission networks on the continent, the paper computes an index that explores spatial and time variations in technical losses in the electricity network as an instrument for electricity shortages. The instrument is combined with geo-referenced data from the Afrobarometer and Enterprise Surveys from more than 20 African countries to estimate the causal impact of electricity shortages on employment, and the mechanisms driving the impact. Results from the paper reveal that electricity shortages exert a substantial negative impact on employment rates in Africa. The evidence also shows three channels by which electricity shortages affect labor market participation. First, on the extensive margin, electricity shortages constrain the creation of new businesses through their negative effect on entrepreneurship. Second, in the intensive margin, electricity shortages reduce the output and productivity of existing firms, thereby causing them to reduce labor demand. Third, electricity shortages act as a distortion in the business climate, thereby reducing the trade and export competitiveness of African firms.